Analisa User Experience Terhadap Customer Loyalty Gopay dengan Trust Sebagai Variable Intervening - Alex Chandra; Fanni Tanisya; Anggellya, Febby; Fiona Livianti; Melisa (Journal of Trends Economics and Accounting Research, 2023)
As time goes on, most of our daily payments can be done cashless or digitally. This has brought a new market for digital payment services, and one of the major players in this industry in Indonesia is GoPay. GoPay is a digital payment service fully integrated with the GoJek application and recently Tokopedia as well. In addition to that, the ability to do QRIS payments directly from the GoJek application has made it very popular, especially among young people who also frequently use services like GoFood, GoRide, or GoCar. However, in this new competitive market, User Experience and Trust are essential for building Customer Loyalty. Therefore, in this study, the author intends to analyze how User Experience and Trust influence Customer Loyalty in the GoPay digital payment application in Batam City. For this study, the data will be collected through questionnaires then be processed using the Structural Equation Modeling (SEM) method. The author successfully obtained 403 sample data from the residents of Batam City through distributed questionnaires, which were then tested by using the SPSS application. Based on the results, the conclusion is that User Experience and Trust have an influence of 0,665 and 0,266 towards Customer Loyalty, and with an influence of 0,642 of User Experience towards Trust in GoPay